One-Step Compared With Two-Step Gestational Diabetes Screening and Pregnancy Outcomes: A Systematic Review and Meta-analysis. Issue 5 (5th November 2022) - Brady, Matthew; Hensel, Drew M.; Paul, Rachel; Doering, Michelle M.; Kelly, Jeannie C.; Frolova, Antonina I.; Odibo, Anthony O.; Barry, Valene Garr; Powe, Camille E.; Raghuraman, Nandini; Tuuli, Methodius G.; Carter, Ebony B.
Abstract : There is no difference in rates of large-for-gestational-age neonates with a one-step testing strategy compared with a two-step testing strategy for gestational diabetes mellitus. Abstract : OBJECTIVE: To estimate short-term maternal and neonatal outcomes with one-compared with two-step testing for gestational diabetes mellitus (GDM). DATA SOURCES: A systematic review of randomized controlled trials (RCTs) and observational studies comparing one-step and two-step GDM testing strategies before September 2021 was conducted. We searched Ovid Medline (1946–), EMBASE (1947–), Scopus (1960–), Cochrane Central, and ClinicalTrials.gov . The primary outcome was rate of large-for-gestational age (LGA) neonates. Secondary outcomes were clinically relevant outcomes for GDM that were selected a priori. METHODS OF STUDY SELECTION: Titles, abstracts, and manuscripts were screened, selected, and reviewed by the first two authors. Four RCTs (24, 966 patients) and 13 observational studies (710, 677 patients) were analyzed. TABULATION, INTEGRATION, AND RESULTS: Pooled relative risks (RRs) were calculated with 95% CIs using random-effects models and were plotted graphically with forest plots. Study heterogeneity was evaluated using Cochran Q and Higgins I 2 tests. The quality of studies that met the inclusion criteria was evaluated with the Downs and Black checklist. Publication bias was assessed by using asymmetry of funnel plots and Harbord's test. There was no difference in the rate of LGA neonates (pooled RR 0.95; 95% CI 0.88–1.04) by testing strategy among RCTs, but patients who underwent one-step testing were more likely to be diagnosed with GDM (pooled RR 2.13; 95% CI 1.61–2.82) and treated with diabetes medications (pooled RR 2.24; 95% CI 1.21–4.15). One-step testing was associated with higher rates of neonatal intensive care unit (NICU) admission (pooled RR 1.12; 95% CI 1.00–1.26) and neonatal hypoglycemia (pooled RR 1.23; 95% CI 1.13–1.34). In analysis of high-quality RCTs and observational studies, one-step testing was associated with a lower rate of LGA neonates (pooled RR 0.97; 95% CI 0.95–0.98), but higher rates of GDM diagnosis, treatment, NICU admission, and neonatal hypoglycemia. CONCLUSION: Despite a significant increase in GDM diagnosis and treatment with one-step testing, there is no difference in rate of LGA neonates compared with two-step testing among RCTs. SYSTEMATIC REVIEW REGISTRATION: PROSPERO, CRD42021252703.